Computerization of libraries of educational institutions in Mindanao - Pellazar, Veronica C.; Pascua, Ma. Divina A.; Esquejo, Nemesio A. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1996)
This study was conducted to find out the status of the computerization of libraries of educational institutions in Mindanao. The chief librarians of each of the 243 libraries of educational institutions in Mindanao as of 1995 were the respondents of the study. The descriptive method was used with questionnaire as a data-gathering tool.
Data obtained from the study showed that out of the 150 respondents only 22 were computerized starting mostly in 1993, while 128 institutions were still planning to computerize. Motivations to computerize are varied. "Goals and objectives of the library/organization" was the main consideration for computerizing. For the libraries that were still planning to computerize, "financial resources" was the main factor which hindered the implementation of their computerization plan. Libraries planned to computerize their operations to solve problems with existing manual system. The priority library areas/functions/services in computerization were cataloging, circulation, and acquisition. Both libraries that were already computerized and those that were still planning to computerize got their funding from a special one-time allocation from their college/university administration. The number one advantage derived from a computerized system was its being "more effective, exhaustive and productive than manual library operations."
Based on these findings, it was concluded that computerization of libraries of educational institutions in Mindanao was still in its infancy.
Typescript.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Academic libraries -- Philippines -- Mindanao -- Automation